Natural products for treatment of osteoporosis: The effects and mechanisms on promoting osteoblast-mediated bone formation - An, Jing; Yang, Hao; Zhang, Qian; Liu, Cuicui; Zhao, Jingjing; Zhang, Lingling; Chen, Bo (Life sciences (1973), 2016)
Osteoporosis is a systemic metabolic bone disease characterized by a reduction in bone mass, bone quality, and microarchitectural deterioration. An imbalance in bone remodeling that is caused by more osteoclast-mediated bone resorption than osteoblast-mediated bone formation results in such pathologic bone disorder. Traditional Chinese medicines (TCM) have long been used to prevent and treat osteoporosis and have received extensive attentions and researches at home and abroad, because they have fewer adverse reactions and are more suitable for long-term use compared with chemically synthesized medicines. Here, we put the emphasis on osteoblasts, summarized the detailed research progress on the active compounds derived from TCM with potential anti-osteoporosis effects and their molecular mechanisms on promoting osteoblast-mediated bone formation. It could be concluded that TCM with kidney-tonifying, spleen-tonifying, and stasis-removing effects all have the potential effects on treating osteoporosis. The active ingredients derived from TCM that possess effects on promoting osteoblasts proliferation and differentiation include flavonoids, glycosides, coumarins, terpenoids (sesquiterpenoids, monoterpenoids, diterpenoids), phenolic acids, phenols and others (tetrameric stilbene, anthraquinones, diarylheptanoids). And it was confirmed that the bone formation effect induced by the above natural products was regulated by the expressions of bone specific matrix proteins (ALP, BSP, OCN, OPN, COL I), transcription factor (Runx2, Cbfa1, Osx), signal pathways (MAPK, BMP), local factors (ROS, NO), OPG/RANKL system of osteoblasts and estrogen-like biological activities. All the studies provided theoretical basis for clinical application, as well as new drug research and development on treating osteoporosis. [Display omitted]